THE EFFECT OF LEARNING MOTIVATION AND SELF-EFFICACY ON ACADEMIC PROCRASTINATION OF CLASS XI AT SMKN 14 JAKARTA - Kholifah, Nur; Yohana, Corry; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the effect of learning motivation (X1) and self-efficacy (X2) with academic procrastination (Y) on students. This study uses quantitative methods with measurements using a Likert scale. In this study, class XI students of SMKN 14 Jakarta were selected as the population with a sample of 161 students. Proportional random sampling technique is a technique used for sampling. This study obtained the results of the hypothesis on the T test and F test. In the T test it resulted in TCount X1 7.583 > TTable 1.97509, it can be said that there is an influence between learning motivation and academic procrastination. Furthermore, TCount X2 4.201 > TTable 1.97509, it can be stated that there is an influence between self-efficacy and academic procrastination. Then the F test produces FCount 28.669 > FTable 3.05, which means that between learning motivation and self-efficacy there is a simultaneous influence on academic procrastination.